Independent Learning in A Classroom-Based Curriculum: Cognitive Strategies and Students’ Self-Confidence in Learning Mathematics - Effendi, Moh. Mahfud; In’am, Akhsanul; Rosyadi, Alfiani Athma Putri; Hamid, Abdul (FKIP Universitas Lampung, 2024)
Abstract: Independent learning is active, initiative and responsible student learning independently. Independent learning can be done in various contexts, where the teaching module is a learning guide. Independent learning requires self-confidence and cognitive strategies in achieving learning goals, and this is difficult to develop in a classroom-based curriculum. On this basis, the aim of this research is to analyze students' cognitive strategies and self-confidence, and determine the influence of cognitive strategies on students' self-confidence in classroom-based independent learning. To achieve the research objectives, the research location was SMAN 8 Malang City with 28 classes consisting of science, social studies and language programs. Meanwhile, the sample was class 12 of the science program which was chosen randomly. To obtain data about students' cognitive strategies and self-confidence, document, questionnaire and interview techniques were used. The data obtained was then analyzed using an interactive and quantitative qualitative approach with regression tests. Based on the results of the analysis, it was found that the use of cognitive strategies was relatively high, while the strategies used were repetition, organization and elaboration respectively. Students' self-confidence is also high, but students lack the courage to express opinions, lack self-concept, and lack responsibility. Simultaneously, this cognitive strategy influences self-confidence, with an influence level of 33.8%, but what has a significant influence is organizational strategy. So it can be said that independent learning is less suitable in implementing a class-based curriculum. Keywords: classroom-based curriculum, cognitive strategies, independent learning, learning mathematics, self-confidence.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp285-299